REFLECTIONS FROM THE MOVING THE LABORATORY ONLINE WORKSHOPS: EMERGING THEMES - Cancilla, Devon A.; Albon, Simon P. (Online Learning, 2008)
How to move science-based labs online has been one of the main obstacles associated with the development of online science programs. In the spring of 2006 and again in 2007, we organized online workshops broadly based around the central theme of Moving the Lab Online. The objective of these workshops was to provide a forum for the exchange of ideas, thoughts, and experience associated with the challenges of moving science labs into the online environment. Produced by Sloan-C, the first workshop, entitled "Practical Techniques for Utilizing Remote Instrumentation to Enhance Science Education" focused primarily on the technical aspects of using remote instrumentation. The second, entitled "Changing the Laboratory Learning Experience Using the Online Environment" looked at issues associated with teaching online labs using remote instrumentation. A number of similar themes emerged from these workshops. These ranged from a need to better articulate the role of the laboratory experience to questions of whether labs even need to be part of the online science learning experience, to the need of the development of best practices. This paper presents the authors’ reflections on the prominent themes and discussions that emerged from the Moving the Lab Online workshop series.